The Role of the MilkLife Soccer Challenge Event in Increasing Interest in Women's Soccer in Semarang City - Fitriana Tsalsa Navila; Tommy Soenyoto (Journal of Physical Education Health and Sport, 2026)
Girls' soccer in Indonesia still faces various challenges, such as gender stereotypes, limited facilities, and limited opportunities for competition. Therefore, organizing sports events specifically for girls' soccer is an important strategy in fostering interest and participation in girls from an early age. This study aims to describe the role of the MilkLife Soccer Challenge Event in increasing interest in girls' soccer in Semarang City. This study uses a descriptive qualitative approach. The research subjects consisted of participants, parents of participants, coaches, and organizers of the MilkLife Soccer Challenge Event, selected using a purposive sampling technique. Data collection techniques included participant observation, in depth interviews, and documentation. Data were analyzed using thematic analysis through data reduction, coding, and conclusion drawing. The results showed that the MilkLife Soccer Challenge Event served as a medium for introducing women's soccer, a source of motivation to play, and a means of building positive experiences and confidence in participants. Organizing factors such as an age based competition system, a variety of activities, and environmental support contributed to strengthening participants' interest in soccer. This study concluded that the MilkLife Soccer Challenge Event served not only as a competition but also as a strategic tool in increasing interest in women's soccer in Semarang City.